Maple tools for modified quaternionic analysis - Falcão, M. I. (2007)
Since 1992 H. Leutwiler, S. L. Eriksson and others developed in a number of papers a modified Clifford analysis and, particularly, a modified quaternionic analysis. The modification mainly consists in considering generalized Cauchy-Riemann equations with respect to a hyperbolic metric in a half space. The aim of this paper is to show how through a change of the basic combinatorial relations used in the modified quaternionic analysis a special Maplesoftware that has been developed for the case of the Euclidean metric can directly be used for numerical calculations in the modified theory.